Estudo experimental da eficácia da publicidade em jogos de tablet - João Paulo Carvalho Pereira Vinagre (2015)
Videogames are becoming, increasingly, the most popular mean of entertainment used by people of all ages. At the same time, product placement is also one of the most important techniques of advertising for marketers of the 21st century. This thesis aims to study the effectiveness of this marketing practice when applied to videogames, specifically regarding aspects like the billboards' size or the brand notoriety. Using a 2D platformer game developed specifically for this work, which was followed by a questionnaire regarding it, it became possible to extract information about how these variables affect the effectiveness of product placement.